International Criminalization of International Terrorizm - A. G. Volevodz (Vestnik MGIMO-Universiteta)
Analysis and studying of the terrorism in all its facets is a complex entangled problem with less clear legal regulation that it might seem at first glance, especially after its transformation from local phenomenon into a world threat. Hitherto terrorism and actions connected to it have been criminalized by the majority of states. There are in modern criminal law whole systems of rules on criminal liability for terrorism which differs considerably from country to country. Terrorism has been criminalized in numerous international regional and universal antiterrorist legal instruments. The author notes that differences in definitions that are enshrined in them hinders international cooperation in criminal matters with respect to terrorist cases. Difficulties reside in the necessity to meet the dual criminality requirement and in the political offense exception. These difficulties can only be overcome through elaboration of a universally recognized definition of the notion of international terrorism and making it legally binding via its inclusion into a universal convention. The issue of definition of international terrorism is an important part of an efficient mutual assistance among states in fight against this crime. In this article the author accounts of actual ways of tackling by the international community of the issue of criminalization of international terrorism and of factors influencing them.